2002
DOI: 10.1007/s00239-001-0078-x
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of DNA Polymerase Families: Evidences for Multiple Gene Exchange Between Cellular and Viral Proteins

Abstract: Abstract.A phylogenetic analysis of the five major families of DNA polymerase is presented. Viral and plasmid sequences are included in this compilation along with cellular enzymes. The classification by Ito and Braithwaite (Ito and Braithwaite 1991) of the A, B, C, D, and X families has been extended to accommodate the "Y family" of DNA polymerases that are related to the eukaryotic RAD30 and the bacterial UmuC gene products. After analysis, our data suggest that no DNA polymerase family was universally conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
211
1
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 225 publications
(219 citation statements)
references
References 37 publications
6
211
1
1
Order By: Relevance
“…A maximum likelihood tree encompassing all the polymerase groups described in (Filee et al, 2002) and trimmed to their specified conserved regions confirmed that metagenomic Clade I-III are not related to the group of phages encoding DNA pol g-like polymerases (Supplementary Figure S5). The clades containing metagenomic representative sequences described in Figure 1 remained distinct and did not disrupt previously established relationships, further supporting our finding that these clades are valid groupings linked to polymerase functionality.…”
Section: Discussionmentioning
confidence: 87%
“…A maximum likelihood tree encompassing all the polymerase groups described in (Filee et al, 2002) and trimmed to their specified conserved regions confirmed that metagenomic Clade I-III are not related to the group of phages encoding DNA pol g-like polymerases (Supplementary Figure S5). The clades containing metagenomic representative sequences described in Figure 1 remained distinct and did not disrupt previously established relationships, further supporting our finding that these clades are valid groupings linked to polymerase functionality.…”
Section: Discussionmentioning
confidence: 87%
“…Indeed, the overall picture becomes more complex when proteins involved in DNA replication, recombination, or repair (DNA informational proteins) are taken into account. The reason is that many DNA informational proteins do not display the classical pattern, i.e., three homologous versions (one for each domain) (18)(19)(20)(21)(22). In particular, the major proteins involved in bacterial DNA replication (DNA polymerase, primase, and helicase) are not homologous to their archaeal͞eukaryal counterparts (i.e., there is only one version of the DnaG primase, the bacterial one, and two versions of the archaeal͞eukaryal primase).…”
Section: The Multiple Versions and Erratic Distribution Of Dna Informmentioning
confidence: 99%
“…The majority of identified DNA polymerases can be classified into Families A, B, C, and Y according to amino acid sequence similarities to Escherichia coli polymerases I, II, III, and IV/V, respectively (4,5). Additional families have been identified, including the two-subunit replicative DNA polymerases from hyperthermophilic Archaea (Family D) (6) and eukaryotic DNA polymerase ␤ and terminal transferases (Family X) (4).…”
mentioning
confidence: 99%